The Effect of Individual Characteristics, Work Placement and Work Environment on Employee Performance (Case Study on PT Post Energy Indonesia Jakarta Office) - Suryanto; Jana Sandra (Perbanas Institute, 2021)
This study aims to determine the effect of individual characteristics, work placement, and work environment on employee performance. There are three independent variables: individual characteristics, work placement, and work environment to be tested for the effect on the dependent variable, namely employee performance. The population in this study were all employees of PT Post Energy Indonesia Jakarta Office, amounting to 114 people. This study used simple random sampling and obtained data from as many as 57 respondents. The research data used are primary data, which is obtained through the distribution of questionnaires. The analytical tool used is the multiple linear regression test. The results showed that: There is a positive and significant influence between Individual Characteristics and Work Environment on Employee Performance, but there is no effect of Work Placement on Employee Performance with a significant value. The coefficient of determination test results shows that the Adjusted R Square value of 40% of the dependent variable on employee performance can be explained by the independent variables, namely individual characteristics, work placement, and work environment. In comparison, other factors of 60% are influenced by other variables outside the variables studied.